2020
DOI: 10.1073/pnas.1820845116
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents’ perceptions of family social status correlate with health and life chances: A twin difference longitudinal cohort study

Abstract: Children from lower-income households are at increased risk for poor health, educational failure, and behavioral problems. This social gradient is one of the most reproduced findings in health and social science. How people view their position in social hierarchies also signals poor health. However, when adolescents’ views of their social position begin to independently relate to well-being is currently unknown. A cotwin design was leveraged to test whether adolescents with identical family backgrounds, but wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 24 publications
4
47
0
Order By: Relevance
“…Older age was also associated with lower levels of both SSS when comparing one's family with the rest of society and when comparing oneself with the rest of the school. This finding is in line with the results of a longitudinal epidemiological study with a British cohort that showed robust correlations between subjective family status and indicators of health such as depression and substance abuse controlling for SES appearing in late adolescence (Rivenbark et al, 2020). Similar findings of decreased SSS with age were found in American adolescents (Amir, Valeggia, Srinivasan, Sugiyama, & Dunham, 2019;Goodman et al, 2007).…”
Section: Discussionsupporting
confidence: 89%
“…Older age was also associated with lower levels of both SSS when comparing one's family with the rest of society and when comparing oneself with the rest of the school. This finding is in line with the results of a longitudinal epidemiological study with a British cohort that showed robust correlations between subjective family status and indicators of health such as depression and substance abuse controlling for SES appearing in late adolescence (Rivenbark et al, 2020). Similar findings of decreased SSS with age were found in American adolescents (Amir, Valeggia, Srinivasan, Sugiyama, & Dunham, 2019;Goodman et al, 2007).…”
Section: Discussionsupporting
confidence: 89%
“…Rivenbark et al (76) demonstrate, in a British birth cohort of mono-and dizygotic twins, how the passage of developmental time can alter associations with mental and physical health endpoints. They find evidence for a "status syndrome" at 18 y of age, in which subjective estimates of family social position in the community are significantly predictive of multiple indicators of mental health and developmental well-being, even with controls for objective socioeconomic status and family environment.…”
Section: Content Of the Special Issuementioning
confidence: 99%
“…Most economists argue that it has risen since the 1960s [ 1 , 2 ]. As a result, researchers have sought to understand the implications of increased income inequality as it affects economic growth [ 3 ], attitudes toward redistributive policies [ 4 6 ], and well-being [ 7 9 ].…”
Section: Introductionmentioning
confidence: 99%